A comparative evaluation of linear dimensional accuracy of the dies obtained using three conceptually different die systems in the fabrication of implant prosthesis: An in vitro study - Manawar Ahmad; Dhanasekar Balakrishnan; Aparna Ichangod Narayan (Wolters Kluwer Medknow Publications, 2014)
Statement of Problem: Given that meticulous implant prosthodontic procedures are recommended to obtain the best possible intraoral fit, the die systems used for multi implant casts warrant further investigation. Die stone expansion and errors introduced by removable die casts may exceed the accuracy required for the passive fit of implant prosthesis. Purpose: The purpose of the study was to evaluate the linear dimensional accuracy between the implant master die and three conceptually different die systems such as Pindex system, Accu-trac precision die system, and Conventional brass dowel pin system. Materials and Methods: Thirty impressions of implant master die were made with polyether impression material. Ten experimental implant casts were fabricated for each of the three different die systems tested: Accu-trac precision die tray system, Pindex system, and conventional brass dowel pin system. The solid experimental casts were sectioned and then removed from the die system 30 times. Linear distances between all six possible distances were measured from one centre of the transfer coping to the other, using a co-ordinate measuring machine in millimeters up to accuracy of 0.5 microns. Data were tabulated and statistically analyzed by Binomial non parametric test using SPSS version 15. Results: Significant differences were found for distance A-B (P = 0.002), A-C ( P = 0.002), A-D (P value = 0.002), and B-D ( P = 0.021) in Conventional Dowel pin system however for Accu-trac precision die tray system, it was significant only for distance A-D (P = 0.002) but for Pindex system it was non-significant for all the distances measured. Conclusion: Within the limitations of this study, use of Pindex system is recommended when sectioned dies are needed for a multi implant retained prosthesis.